A Single Test, A Double Threat: Pulmonary Embolism and Coronary Stenosis Diagnosed with TRO-CT: Case Report - Aflakha, Zakiyyatul; Muzakky Misbachul F, Much.; Ardiana, Meity; Nugraha Teguh Palin, Nugraha Teguh Palin; Cornelia Ghea, Cornelia Ghea (Journal of Neonatal Surgery, 2025)
Pulmonary embolism (PE) and coronary stenosis are cardiovascular conditions with overlapping pathophysiological pathways, including coagulation activation, systemic inflammation, and endothelial dysfunction. This case presents an opportunity to explore the complex relationship between concurrent PE and coronary stenosis while evaluating the most effective diagnostic strategies for their simultaneous identification and management. Case presentation: A 77-year-old male with a history of ischemic stroke presented with worsening dyspnea and chest discomfort. The patient was discharged after hospitalization for non-ST-elevation acute coronary syndrome (NSTEACS) without revascularization. Discussions: This case report highlights the simultaneous occurrence of pulmonary embolism (PE) and coronary stenosis, emphasizing the diagnostic and therapeutic challenges. We utilized Triple-rule-out Computed Tomography (TRO CT) to effectively detect both coronary stenosis and pulmonary embolism in a single imaging examination, enabling simultaneous diagnosis of these conditions. TRO CT is a highly valuable diagnostic tool in cases of complex chest pain, particularly when the underlying cause is unclear and may stem from multiple etiologies. Special emphasis is placed on distinguishing between type I and type II myocardial infarction, elaborating on the different diagnostic approaches for each type and underscoring the importance of accurate identification to determine the most appropriate therapeutic strategy. Conclusions : This case report highlights the utility of Triple Rule-Out Computed Tomography (TRO CT) in simultaneously diagnosing pulmonary embolism (PE) and coronary stenosis in patients with complex chest pain.